PERAN PEREMPUAN DALAM LEMBAGA TUHA PEUT SEBAGAI LEMBAGA ADAT ACEH DAN PEMERINTAHAN GAMPONG - Fauzi Abubakar (AL-TAHRIR, 2015)
Abstract: This study was aimed at assessing the role of women in the discourse of feminism which was not only in the form theoretical talks and debates but also practical ones in various parts of the world, including in Aceh, Indonesia. In practical level, the role of women had played in various institutions such as in  traditional/conventional institutions and government ones. The focus of the problem was how the role of women in traditional institutions 'Tuha Peut' and  the local government of Aceh were. Through a historical approach, this paper tried to explore the role of women in traditional institutions 'Tuha Peut' and local government in Aceh. Based on the various data collected such as observation, interviews and documentation, it showed that the role of women in institutions of Tuha Peut, as a traditional institution of Aceh and a government administrator of Gampong Aceh, was equal to the role of men, especially in formulating policies in Gampong. Data also showed that women had more prominent role, especially in efforts to achieve policies on the equity of gender. Acehnese women could not only give advice and consideration to Keuchik (head of the alliance of indigenous peoples of Gampong) but also could give supervision to the Reusam Gampong. Women also could become a mediator to resolve the conflicts that arised in Aceh through the consultation of indigenous peoples and offering a solution for the sake of ending the conflict properly without taking the formal and official legal justice.الملخص :أصبح دور المرأة – في فكرة النسوية – حديثا ليس فقط نظريا بل تطبيقيا في كثير من أنحاء العالم ومنها في أتشيه، إندونيسيا. وفي التطبيق، كان دور المرأة في شتّى المؤسسات،  مؤسسة عادة أو حكومة. كان تركيز المسألة في هذه الدراسة هي كيف يكون دور المرأة في مؤسسة العادة "Tuha Peut" والحكومة في أتشيه.  حاولت هذه الدراسة – بالمدخل التاريخي – دراسة دور المرأة في مؤسسة العادة "Tuha Peut" والحكومة . دلّت البيانات – المحصولة عليها عن طريق الملاحظة، والمقابلة، والوثائق المكتوبة – على أن دور المرأة في مؤسسة العادة "Tuha Peut" أو الحكومة القائمة "Gampong"متوازيا بدور الرجل، خاصة في تصميم القرارات. ودلّت البيانات كذلك على أن دورها أكثر وضوحا وخاصة فيما يتعلق بالقرارات المتعلقة بالجنس. إن المرأة –ليس فقط- قادرة على تقديم الآراء والاعتبارات إلى "Keuchik" (رئيس اتحاد مجتمع العادة Gampong) بل قادرة على القيام بالملاحظة والتفتيش تجاه Reusam Gampong . واستطاعت المرأة كذلك أن تكون همزة وصل لحل المنازاعات والخلافات بين مجتمع العادة أتشيه عن طريق الاستشارة وطرح سبيل الحل لحل هذه الخلافات حتى لا يكون حلّها عن طريق المحكمة.Abstrak: Peran perempuan dalam wacana feminisme tidak saja menjadi perbincangan teoritis tetapi juga praktis di berbagai belahan dunia, termasuk di Aceh Indonesia. Dalam tataran praktis, peran perempuan berada dalam berbagai institusi baik institusi adat maupun pemerintahan. Fokus masalahnya adalah bagaimana peran perempuan dalam institusi adat ‘Tuha Peut’ dan pemerintahan di Aceh. Melalui pendekatan sejarah, tulisan ini mencoba untuk mengeksplorasi peran perempuan dalam institusi adat ‘Tuha Peut’ dan pemerintahan di Aceh. Beragam data, melalui observasi, interview dan dokumentasi, menunjukkan bahwa peran perempuan dalam institusi Tuha Peut baik sebagai institusi adat Aceh maupun penyelenggara pemerintahan Gampong memiliki peran yang setara dengan laki-laki khususnya dalam merumuskan kebijakan Gampong. Data juga menunjukkan bahwa peran perempuan lebih menonjol terutama dalam upaya mewujudkan kebijakan yang berkeadilan gender. Perempuan Aceh tidak saja dapat memberi saran dan pertimbanga kepada Keuchik (kepala persekutuan masyarakat adat Gampong) tetapi juga dapat melakukan pengawasan terhadap Reusam Gampong. Perempuan juga dapat menjadi mediator penyelesaian konflik yang muncul dalam masyarakat adat Aceh melalui konsultasi dan tawaran solusi demi terselesaikannya konflik dengan baik tanpa menempuh jalur peradilan formal. Keywords: perempuan, institusi adat, pemerintahan Gampong, Tuha Peut, Reusam Gampong, mediator.